Predicting Behavioral Intentions to Prevent or Mitigate COVID-19: A Cross-Cultural Meta-Analysis of Attitudes, Norms, and Perceived Behavioral Control Effects. Issue 1 (January 2022) - Fischer, Ronald; Karl, Johannes Alfons
We examined the effectiveness of attitudes, subjective norms, and perceived behavioral control (PBC) of the theory of planned behavior on COVID-19 relevant behavioral intentions and behaviors. We conducted a meta-analysis of 335 effect sizes from 83 samples across 31 countries ( N = 68, 592). We found strongest effects for PBC, but contrary to previous research also moderately strong effects of subjective norms. Focusing on systematic context effects: (a) norm–behavior associations at individual level were strengthened if population norms were stronger; (b) collectivism strengthened norm effects in line with cultural theories, but also attitude and PBC associations, suggesting that COVID-relevant behaviors show collective action properties; (c) in line with cultural theory, tightness–looseness strengthened normative effects on behaviors; and (d) contrary to post-modernization theory, national wealth weakened attitude and PBC associations. These analyses provide new theoretical and practical insights into behavioral dynamics during an acute public health crisis.